Invasion mechanisms of Gram-positive pathogenic cocci - Nitsche-Schmitz, D Patric; Rohde, Manfred; Chhatwal, Gursharan S (Thrombosis and haemostasis, 2007)
Gram-positive cocci are important human pathogens. Streptococci and staphylococci in particular are a major threat to human health, since they cause a variety of serious invasive infections. Their invasion into normally sterile sites of the host depends on elaborated bacterial mechanisms that involve adhesion to the host tissue, its degradation, internalisation by host cells, and passage through epithelia and endothelia. Interactions of bacterial surface proteins with proteins of the host's extracellular matrix as well as with cell surface receptors are crucial factors in these processes, and some of the key mechanisms are similar in many pathogenic Gram-positive cocci. Therapies that interfere with these mechanisms may become efficient alternatives to today's antibiotic treatments.